IMPLEMENTATION OF INVENTORY METHOD IN IMPROVING VISUAL STUDENTS VISUAL LEARNING ON NATURAL RESPONSIBILITY RESOURCES AND ENVIRONMENTAL SURVIVAL - Tresna Nurhayati (IKIP Siliwangi, 2017)
The main issues of this research are how to improve the visual abilities of Elementary School (ES) students on Natural Resources (NR) and Environment (EN) subjects through the method of discovery. The objectives of the research are as follows: (1). Improving visual abilities of elementary students through discovery methods; (2). Provides learning through fun discovery methods and can inspire elementary students. The methods / approaches used in achieving the following objectives: (a). Collect students and elementary teachers involved in research; (B). Provide an overview of the research activities to be undertaken; (C). Reflecting on, discussion of learning by method of discovery; (D). Collaborate with elementary teachers in the determination of experimental class and control class; (E). Implementation of learning method of discovery; (F). Evaluation of learning by method of discovery. The results showed that there was an increase in visual ability of elementary school students through learning with the method of discovery of 24%; (2). Elementary students are enthusiastic about learning by the method of discovery given by the teacher; (3). The occurrence of collaboration between one student and another student at the time of learning by the method of discovery is done. Keywords: Learning, Invention Method, Visual